TREATMENT OF ABFRACTION LESION WITH TYPE II GLASS IONOMER CEMENT - Widya Wijayanti; Endang Suprastiwi (Faculty of Dentistry, Universitas Indonesia, 2015)
Abfraction is a loss of tooth structure at the cervical area, which is caused by tensile and compressive strength. The loss of enamel may expose the dentin and will result in hypersensitivity of dentin and affects pulp vitality. The diagnosis could be identified in the presence of wedge shaped lesion, facet on the occlusal surface, usually affected one tooth only, and the presence of heavy occlusal loads. This lesion could be restored by a conventional glass-ionomer cement which has similar elasticity to the dental hard tissue and accompanied by occlusal adjustment.